KONTRIBUSI KELENTUKAN OTOT PUNGGUNG DAN DAYA LEDAK OTOT TUNGKAI TERHADAP HASIL HEADING SEPAK BOLA SISWA PUTRA EKSTRAKURIKULER SMK NEGERI 7 PEKANBARU - Al Ketri Laiga; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine whether there is a relationship between back muscle flexibility and leg muscle explosive power on the results of headings on male extracurricular students of SMK Negeri 7 Pekanbaru. The place of this research was conducted in the field of SMK Negeri 7 Pekanbaru on Jln. Yossudarso Rumbai was conducted from November 2019 to April 2020. The sample in this study was a total population of 19 people. Based on the results of research and data processing using statistical procedures, it was concluded that there was a significant contribution between back muscle flexibility and leg muscle explosive power with soccer heading results where Rx1x2 (there is contribution of back muscle flexibility and leg muscle explosive power) = count 0.96 and the contribution is 92.16% Rx1y (there is contribution of back muscle flexibility with soccer heading capabilities) = 0.94 count and 88 contributions 36%. Rx2y (there is a contribution of leg muscle explosive power to the ability of soccer headings) = rcount of 0.96 and its contribution is 92.16%. Rx1x2y (there is a contribution of back muscle flexibility and leg muscle explosive power with the ability of soccer headings) = a calculation of 0.962 and a contribution of 92.54%Key Words: Back Muscle Strength, Leg Muscle Explosion Power, Heading